Variations In Expressive Speech Acts By Age In Buying And Selling Transactions At The Labuapi Traditional Market In West Lombok - Muhamad Sahril; Rudi Arrahman; Supratman Supratman; Habiburrahman Habiburrahman (Jurnal Ilmiah Mandala Education (JIME), 2026)
This study aims to describe variations in expressive speech acts based on age in buying and selling transactions at Labuapi Market, West Lombok. The approach used is qualitative descriptive, with a focus on pragmatic analysis. The research data consists of utterances between sellers and buyers containing expressive speech acts, collected through observation, recording, transcription, and interviews. The research subjects were grouped into three age categories: youth, adults, and the elderly. The results indicate that various forms of expressive speech acts-such as praise, complaints, expressions of gratitude, apologies, and criticism-are used in buying and selling interactions. The variation in the use of expressive speech acts is influenced by age, as the youth group tends to use language that is more spontaneous, informal, and expressive. The adult age group demonstrated a more balanced use of language between expression and politeness, while the elderly age group placed greater emphasis on politeness and formality in speech. However, age is not the sole determinant, as situational context, communication goals, and social roles also influence the use of expressive speech acts. This study contributes to the field of pragmatics, particularly in understanding language variation within the context of social interaction in traditional markets.